The immune response of the human brain to abdominal surgery. Issue 4 (11th April 2017) - Forsberg, Anton; Cervenka, Simon; Jonsson Fagerlund, Malin; Rasmussen, Lars S.; Zetterberg, Henrik; Erlandsson Harris, Helena; Stridh, Pernilla; Christensson, Eva; Granström, Anna; Schening, Anna; Dymmel, Karin; Knave, Nina; et al.
Abstract : Objective: Surgery launches a systemic inflammatory reaction that reaches the brain and associates with immune activation and cognitive decline. Although preclinical studies have in part described this systemic‐to‐brain signaling pathway, we lack information on how these changes appear in humans. This study examines the short‐ and long‐term impact of abdominal surgery on the human brain immune system by positron emission tomography (PET) in relation to blood immune reactivity, plasma inflammatory biomarkers, and cognitive function. Methods: Eight males undergoing prostatectomy under general anesthesia were included. Prior to surgery (baseline), at postoperative days 3 to 4, and after 3 months, patients were examined using [ 11 C]PBR28 brain PET imaging to assess brain immune cell activation. Concurrently, systemic inflammatory biomarkers, ex vivo blood tests on immunoreactivity to lipopolysaccharide (LPS) stimulation, and cognitive function were assessed. Results: Patients showed a global downregulation of gray matter [ 11 C]PBR28 binding of 26 ± 26% (mean ± standard deviation) at 3 to 4 days postoperatively compared to baseline ( p  = 0.023), recovering or even increasing after 3 months. LPS‐induced release of the proinflammatory marker tumor necrosis factor‐α in blood displayed a reduction (41 ± 39%) on the 3rd to 4th postoperative day, corresponding to changes in [ 11 C]PBR28 distribution volume. Change in Stroop Color‐Word Test performance between postoperative days 3 to 4 and 3 months correlated to change in [ 11 C]PBR28 binding ( p  = 0.027). Interpretation: This study translates preclinical data on changes in the brain immune system after surgery to humans, and suggests an interplay between the human brain and the inflammatory response of the peripheral innate immune system. These findings may be related to postsurgical impairments of cognitive function. Ann Neurol 2017;81:572–582